GREEN SUPPLY CHAIN: PROTAGONISTA OU COADJUVANTE NO BRASIL? - Ana Paula Ferreira Alves; Luis Felipe Machado do Nascimento (RAE: Revista de Administração de Empresas, 2014)
Environmental issues began to be introduced more frequently in corporate business. As for the supply chain, Green Supply Chain Management (GSCM) emerges as a new approach to corporate responsibility towards the environment. This article aims to analyze the diffusion of the GSCM concept and practices in the Brazilian scenario. To do that, we conducted interviews with experts on the subject of the supply chain in the area of Management in Brazil. The results show that the reasons for the slow development of the concept may relate to characteristics of the domestic market, corporate focus on internal aspects, lack of strict legislation, and low consumer pressure. Experts notice, however, good prospects for the future of discussions on the subject in the Country, due to the National Solid Waste Policy, pressure from the international market, and the search for environmental certification. This study sought to foster further discussions on GSCM in Brazil.